Risk stratifying the screening of Barrett's esophagus: An Asian perspective. Issue 2 (11th October 2017) - Sharma, Neel; Hui, Tianyi; Wong, Hung C; Srivastava, Supriya; Teh, Ming; Yeoh, Khay G; Ho, Khek Y
Abstract : Background and Aim: Barrett's esophagus (BE) is a premalignant condition for esophageal adenocarcinoma. Although risk factors exist for screening patients in the West, we aimed to determine the factors in terms of demographics and symptoms for patients in an Asian setting. Methods: We recruited 1378 patients over a 7‐year period as part of an ongoing gastric cancer screening program. An appropriately designed questionnaire was utilized to determine the necessary risk factors and symptoms with endoscopic analysis and subsequent histological confirmation as the gold standard. We utilized the existence of intestinal metaplasia of the distal esophagus as the primary diagnostic pathology. Results: We demonstrated that no symptoms were indicative of BE in an Asian setting. Age (odds ratio 1.081, 95% confidence interval 1.022–1.143) and male gender (odds ratio 4.808, 95% confidence interval 1.727–13.33) proved significant demographic factors for the presence of intestinal metaplasia ( P 0.007, 0.003, respectively). Conclusions: We advocate the utilization of increasing age and male gender as the primary risk factors for patients at risk of BE. We also recommend astute examination of the distal esophagus whilst patients undergo simultaneous gastric cancer screening. Abstract : This study aimed to analyse the symptoms and risk factors associated with the development of Barrett's oesophagus in an Asia setting. We noted that symptoms were non specific and advise for more astute analysis of the distal oesophagus in order to pick up those patients at risk.